Measuring the Impact of a Summer Pre-Kindergarten Program on Academic Gains and School Readiness: Success by Six! - Debra Gratz; Karen H Larwin (Institute of Advanced Engineering and Science, 2014)
Early intervention prior to kindergarten is an effective strategy in closing the gaps in pre-readiness skills and appropriate behavior which may occur because of disparity in socioeconomic status, parenting styles, and preschool experience. This current investigation was designed to determine if the pre-kindergarten intervention had an impact on the student success in kindergarten. At the end of the academic year, results reveal that the achievement gap for students who were academically delayed was diminished; no significant differences exist between academically delayed students relative to students not identified as academically delayed. Results reveal that the impact of socioeconomic status was also diminished for participants in the summer pre-kindergarten program.DOI: http://dx.doi.org/10.11591/ijere.v3i1.5577